Implementasi Peraturan Bupati Nomor 9 Tahun 2021 tentang Tata Cara Penghapusan Piutang Pajak Bumi Bangunan Perdesaan dan Perkotaan (PBB-P2) yang Sudah Kedaluwarsa di Kabupaten Dharmasraya Menurut Siyasah Tanfiziyah - Sherly Yunita; Helfi Helfi (Lembaga Yasin AlSys, 2026)
This study was motivated by the accumulation of overdue Rural and Urban Land and Building Tax (PBB-P2) receivables in Dharmasraya Regency for approximately 16 years, particularly receivables originating from the period before regional expansion and no longer collectible because they had exceeded the time limit stipulated in tax regulations. This condition created administrative problems, affected the quality of regional financial reports, and encouraged the local government to enact Regent Regulation Number 9 of 2021 concerning the procedure for writing off overdue PBB-P2 receivables. However, its implementation still shows discrepancies between policy provisions and field realization, particularly regarding the implementation deadline. This study aims to analyze the implementation of Regent Regulation Number 9 of 2021 and review it from the perspective of siyasah tanfiziyah, particularly in the aspects of justice, trustworthiness, and public benefit. This study used field research with a descriptive qualitative approach. Data were obtained through interviews with relevant informants, namely the Legal Division of the Regional Secretariat, the Regional House of Representatives, and the Regional Finance Agency, as well as documentation in the form of archives, documents, and decrees on the write-off of receivables. The data were analyzed through the stages of data collection, data reduction, and conclusion drawing. The results showed that policy implementation had proceeded according to procedure and reflected the principle of accountability. From the perspective of siyasah tanfiziyah, this policy has fulfilled the principles of justice, trustworthiness, and public benefit, although obstacles remain in the form of incomplete data, changes in administrative regions, limited resources, and suboptimal interinstitutional coordination. The conclusion of this study affirms that the write-off of overdue PBB-P2 receivables is an important administrative and legal measure for improving regional financial governance. These findings contribute to the development of public policy studies and Islamic constitutional law and have practical implications for local governments in strengthening accountability, coordination, and accuracy in implementing regional receivables write-off policies.